Comparison of Sanctions for the Criminal Act of Robbery in Islamic Jurisprudence and Indonesian Criminal Law - Khairun Nisa; Adella Nurul Azzahra; Alya Syafa; Zulkarnain Tuanku Lelo; Annawawi Fairuzi (Jurnal Sahabat ISNU SU, 2024)
Robbery is a crime that frequently occurs in society and causes both material and psychological losses to victims. From an Islamic legal perspective, robbery is known as hirabah, which is the act of taking another person's property with violence or threats that instill fear in the community. Meanwhile, Indonesian criminal law regulates robbery as theft with violence as stipulated in Article 365 of the Criminal Code (KUHP). This study aims to analyze and compare the sanctions for the crime of robbery in Islamic jurisprudence (fiqh jinayah) and Indonesian criminal law. This study uses a normative legal research method with a statutory and comparative legal approach. Data were obtained through a literature review of the Qur'an, hadith, Islamic jurisprudence books, laws and regulations, and relevant scientific literature. The results show that Islamic jurisprudence stipulates hudud sanctions based on the level of crime committed by the perpetrator, while Indonesian criminal law applies imprisonment, life imprisonment, and the death penalty in certain circumstances. Despite differences in the form of sanctions, both legal systems have the same goal, namely to protect society, maintain public order, and provide a deterrent effect on perpetrators of criminal acts.